Financial regressivity: investigating the economic impact during the COVID-19 coronavirus pandemic on the brazilian family (Research, Society and Development, 2021)
The objective of this research was to investigate the economic impact on the beginning of the COVID-19 coronavirus pandemic on the Brazilian family. The study is characterized as quantitative and qualitative descriptive and/or exploratory. In addition, it has a field research design, using as a data collection instrument a pre-structured questionnaire with 19 objective questions, divided into two categories: (a) profile or personal data; and (b) the financial impact caused by the COVID-19 pandemic. The scoring method was used to define the indebtedness trend of individuals. From the sampling unit (n=336 respondents), the financial unpreparedness of the vast majority of respondents to face the pandemic was evident. However, a considered percentage has financial reserves for an emergency period. At the beginning of the pandemic, most of the interviewees' families had their monthly income reduced, making cuts necessary to maintain financial control. From then on, the expenses prioritized during the pandemic period would be food and health. With only two months of the beginning of isolation in Brazil, a percentage of 13.7 of respondents had incurred debt due to the needs that arose from the pandemic: 73.5% and 26.5% of these are below and above the average debt score, respectively. Interestingly, 24.1% of respondents have doubts and 4.8% do not intend to save resources for possible contingencies after this pandemic moment. Conclusively, Brazilian families are not financially prepared to face emergency situations such as a pandemic and that this lack of preparation is associated with a lack of financial education.